A Durable, Flexible, Large‐Area, Flame‐Retardant, Early Fire Warning Sensor with Built‐In Patterned Electrodes. Issue 4 (18th January 2021) - Khan, Fawad; Wang, Shanchi; Ma, Zhewen; Ahmed, Adnan; Song, Pingan; Xu, Zhiguang; Liu, Riping; Chi, Huanjie; Gu, Jiayi; Tang, Long‐Cheng; Zhao, Yan
Abstract: Fire has been giving rise to enormous loss of life and property worldwide annually. Early fire warning represents an active and effective means to avoid potential fire hazards before huge losses occur. Despite encouraging advances in early fire warning systems, to date there remains an urgent lack of the design of a durable, flexible, and universal early fire warning sensor for large‐area practical applications. Herein, facile fabrication of a durable, flexible, large‐scale early fire‐warning sensor is demonstrated through constructing a hierarchical flame retardant nanocoating, composed of graphene oxide, poly(dimethylaminoethyl methacrylate), and hexagonal boron nitride, on cotton fabric in combination with the parallelly patterned conductive ink as built‐in electrodes. As‐designed large‐scale sensor (>33 cm and extendable) exhibits a short alarming time of <3 s in response to external abnormal high temperature, heat, or fire. In addition to high washability, flexibility, resistance to abrasion and wear, this hierarchical nanocoating can self‐extinguish, thus enabling the sensor to continue warning during fire. This work offers an inventive concept to develop a universal and large‐scale very early fire‐monitoring platform, which opens up new opportunities for their practical applications in effectively reducing fire‐related casualties and economic losses. Abstract : A strategy is proposed to fabricate a new type of large‐area early fire warning sensor by patterning fire‐sensing, flame‐retardant, GO‐based coating and conductive ink in an interdigitated way on cotton fabrics. The sensor features a rapid response (<3 s), and is flexible, washable, and mechanically durable, demonstrating its great promise for very early fire warning.